2021
DOI: 10.4269/ajtmh.21-0463
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene and Mask-Wearing Practices during COVID-19 among Healthcare Workers: Misinformation as a Predictor

Abstract: Poor public health information is a hurdle in infectious disease control. The study aims to examine whether healthcare workers adhere to hand hygiene and mask-wearing guidelines during the COVID-19 pandemic and to explore their exposure to misinformation about the pandemic as a predictor. A cross-sectional survey was sent to 518 healthcare workers across Indonesia, the fourth largest nation in the world, in September 2020 during the COVID-19 pandemic. The respondents reported whether they adhered to the guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…For instance, a study in Indonesia reported an overall practice of 51.5% among university students (69), in line with findings from Ethiopia (70). Most participants reported wearing facemasks in public, which corroborate findings from other studies (69,73). However, the current findings are higher than those reported by Kateule and others in an observational study where 24% of the participants wore masks in Lusaka district and 27% wore masks in Mansa district of Zambia (74).…”
Section: Discussionsupporting
confidence: 90%
“…For instance, a study in Indonesia reported an overall practice of 51.5% among university students (69), in line with findings from Ethiopia (70). Most participants reported wearing facemasks in public, which corroborate findings from other studies (69,73). However, the current findings are higher than those reported by Kateule and others in an observational study where 24% of the participants wore masks in Lusaka district and 27% wore masks in Mansa district of Zambia (74).…”
Section: Discussionsupporting
confidence: 90%
“…More than a two-third of studies investigated general HCWs and the general population to generate more meta-analytical evidence, which suggests that policymakers and health care organizations need to further prioritize frontline HCWs and students in this ongoing pandemic. Medical (including nursing) students [ 79 ] are worthy of special attention.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that there is high individual-level heterogeneity in willingness to comply with COVID-19 preventive behaviors such as mask-wearing and hand hygiene among the general population as well as among healthcare workers ( 34 , 35 ). Uncertainty and limited information are particularly problematic as they can make healthcare professionals prone to misinformation, which is in turn associated with noncompliance with preventive behaviors ( 35 ), reduce the quality of care, and increase their fear, anxiety, and stress ( 36 ).…”
Section: Discussionmentioning
confidence: 99%